Norsk kulturhistorie i kontekst - et bidrag til genealogien - Rogan, Bjarne (Tidsskrift for kulturforskning, 2015)
The article endeavours to give a broad historiographical overview of cultural history in Norway and to some extent in Scandinavia, covering a century from ca. 1880. The point of departure is the jungle of variants of ’new cultural history’ and the fact that the roots of Scandinavian cultural history deviate considerably from other national traditions. The text briefly reviews the different concepts of culture as a background and then discusses the work of three Scandinavian pioneers who all published around 1880 (Troels Troels-Lund, August Strindberg and Yngvar Nielsen). Next is presented the local history move-ment with its academic elite researchers and its broad grass-root movement, as well as the open-air museum ’paradigm’. The focus then shifts to the rich written literature of cultural history and the voluminous book series published during the century, some of them with a national Norwegian scope, some with a Nordic scope, and one with a global scope. Finally the text presents brief outlines of the two foremost cultural history disciplines (in addition to history and art history), namely ethnology and folklore. In all these fields and across these arenas of cultural history, with their porous frontiers and overlapping approaches, the Norwegian tradition appears as closely knit to themes like popular tradi-tions and beliefs, customs and usage, material culture, everyday life and work. It also appears that the roots of cultural history blend with national and local identity projects and a political nationalism.